Systematic review of student engagement instruments in higher education: Evaluating reliability, applicability, and comprehensive coverage across diverse factors - Pang, Jieyu; Aziman, Abdullah (The International Academic Forum (IAFOR), 2025)
Numerous student engagement instruments have been introduced in higher education (Heilporn et al., 2024), yet selecting an instrument that effectively addresses the key areas of student engagement, including behavior, cognitive, emotions, social interactions, and active participation remains a challenge. This paper aims to examine the recent research on student engagement instruments in higher education, identifying their strengths and weaknesses using PRISMA guidelines. A literature search conducted in the Scopus database resulted in the inclusion of 23 articles. These articles traced back 17 different types of instrument questionnaires to their original sources, which were then examined. The findings reveal that all instruments exhibit high reliability and are suitable for both male and female students. Additionally, most instruments, specifically 78% are appropriate for university-level education and 61% of the instruments are appropriate for any course. However, significant weaknesses were identified. 78% of the instruments are not applicable across all course modalities, 61% are not suitable for all age groups, and 61% percent do not apply to all faculties. Among the reviewed instruments, one stands out for its inclusiveness and high reliability. It effectively supports students of all ages, genders, subjects, faculties, and course modalities at the university level while comprehensively covering the five dimensions of student engagement. This review highlights the need for more inclusive and adaptable instruments in higher education to ensure comprehensive measurement of student engagement across diverse contexts.